“Basic English”: An Android-Based Teaching Media for Students Grade 7th Built-in Construct 3 - Deby Mega Rizkia Riesna; Sigit Sugiyanto; Tito Pinandita (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
The use of technology and information in Indonesia is widely spread. Various groups have been reached with gadgets that are pretty sophisticated and can be used for multiple purposes, not only for sending messages or news, listening to music, watching videos or films, and playing online games but can also be used as learning media, especially after the COVID-19 outbreak hit Indonesia. For about two years, educational facilities in Indonesia have been running online. Unfortunately, the use of technology in education is still not optimal. This research aims to help teachers and students optimize technology use in supporting learning and teaching activities. Using Construct 3, an application to learn English for grade 7 students of SMP/MTs was successfully created. The Basic English game contains a summary of material and practice questions that can be accessed and operated using Android on students' cell phones anywhere and anytime.